Green public procurement in the most visited European museums: A comparison and a mapping - Michal Plaček; Jordi Rosell; Vladislav Valentinov; Milan Křápek (Humanities and Social Sciences Communications, 2024)
While scholarly research on green public procurement (GPP) keeps growing, until now it has paid little attention to museums that must make decisions about GPP implementation. This paper breaks new ground by exploring GPP implementation in the most visited European museums. The proposed conceptual framework allows a comparison and a mapping of museums' GPP implementation levels while taking account of how these levels are related to the national GPP performance. Complementing this framework with the analysis of the up-to-date data from the Tender Electronic Daily database yields two central findings. First, museums that formalized their GPP policies in their strategic organizational documents exhibit higher levels of GPP implementation than other museums that have not done so. Second, the majority of the investigated museums follow national trends of GPP implementation, with examples of exceeding or falling below these trends being rare. The article is important for policy makers and practitioners as it highlights the importance of the factor of institutionalization of green procurement in individual organizations, which is crucial for successful implementation of green procurement.
Keywords: 630